209- إدارة الجودة الشاملة وتطبيقها فى تقييم بعض قطاعات المرافق العامة فى مصر / Total Quality Management and its Application in the Evaluation of the Performance of Several Sectors in Public Utilities in Egypt - محرم الحداد; حسام المندور; اجلال راتب; ماجدة ابراهيم; زلفى شلبي; وأخرون (معهد التخطيط القومي،, 2018)
سبتمبر 2008.